Effectiveness of Google Sites–Assisted Problem-Based Learning in Enhancing Students’ Critical Thinking on Heat and Temperature - Damayanti, Sherly Eka Putri; Purwaningsih, Endang; Suwasono, Purbo (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to analyze the effectiveness of the Google Sites-assisted Problem-Based Learning (PBL) model in improving students’ critical thinking skills on temperature and heat topic. The PBL model was selected because it emphasizes problem-solving and active student participation in learning. Its strength lies in training students to think logically, collaborate, and develop solutions through direct experiences. However, PBL often faces challenges such as limited time, insufficient contextual learning resources, and a lack of media that support independent learning. To address these limitations, this study integrates PBL with Google Sites as a technology-based learning platform. The use of Google Sites provides flexible, engaging, and easily accessible learning resources that enhance students’ readiness before class. It serves as a medium for presenting materials, guiding activity steps, offering interactive simulations, and providing spaces for reflection. This integration allows students to build conceptual understanding independently and participate more effectively in classroom learning. The novelty of this study lies in the use of Google Sites not merely as a supporting tool but as a digital learning environment that strengthens the orientation of students’ critical thinking. A quantitative method with a quasi-experimental design (pretest–posttest control group design) was employed, involving two classes: an experimental class using the PBL model assisted by Google Sites and a control class applying the Direct Instruction model. The results showed that the Google Sites-assisted PBL model was more effective in improving students’ critical thinking skills, independence, and active engagement compared to the Direct Instruction model.